Entre o medo e o fascínio: televisão e formação da crítica televisiva na imprensa (1964-1982) - Menezes, Milena Azevedo de (2022)
The present research aims to analyze the historical construction of writing about TV between the years 1964 and 1984 in Brazil, published in cultural sections of the press. Our object of study is the formation of television criticism, understood as a debate of visions of the future about television, between fear and fascination. The research is situated in the methodological perspective recognized as social history of culture. According to Raymond Williams (2017), television as a technology results from a series of socially motivated inventions, rejecting the deterministic perspective and understanding TV as a "cultural form." We will analyze the following printed media: Jornal do Brasil, Tribuna da Imprensa, Última Hora Magazine, Folha de S. Paulo and O Globo as primary sources. Throughout the research, secondary sources were situated, such as pamphlet magazines and the alternative press. The objective of the time cut is to situate the intellectual debates by leftist critics responsible for producing the construction of the category "mass culture" and "cultural industry" in the printed press, during the civil-military dictatorship. Finally, at the end of the research, we understand the debates published about TV within the historicity of the moment in which television is inserted into Brazilian society, from the formation of an entertainment industry, which grows in its audience and is incorporated into everyday life during the civil-military dictatorship.